Hydrodynamics and liquid phase residence time distribution in mesh microreactor - Kulkarni, A. A.; Gorasia, A. K.; Ranade, V. V. (Chemical Engineering Science, 2007)
This paper is focused on the experimental analysis of residence time distribution and phase hold-up in a mesh microreactor. A microreactor, where a finely weaved mesh is sandwiched between two flat plates with specific inlets for gas and liquid, is proposed. The microvolumes formed upon sandwiching the mesh are totally connected and thus it yields a view of several interconnected microvolumes. This system is easy to build and does not need precision micromachining. A high-speed photographic analysis yielded the phase distribution for different mesh types over a wide range of operating gas and liquid flow rates. The RTD was studied by measuring the liquid phase conductivity at the outlet of the reactor. Channeling prevailed for mesh with smaller open area. The ADEM was used for fitting the tracer curves with tailing ends. The RTD and the image analysis for all the mesh types showed hysteresis when the gas flow rate was maintained constant and the liquid flow rate was gradually increased and then decreased. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: hydrodynamics; hysteresis; image analysis; microreactor; residence time distribution

Singlejet fluidized beds: experiments and CFD simulations with glass and polypropylene particles - Utikar, Ranjeet P.; Ranade, Vivek V. (Chemical Engineering Science, 2007)
Understanding hydrodynamics of bubbling fluidized beds is crucial in proper design and scale up of these beds. CFD models have shown promise in gaining this understanding. In order to generate confidence in CFD models, predicted time averaged and dynamical characteristics of the bubbling fluidized beds need to be validated against experimental data. This paper describes such studies with rectangular fluidized beds operated with a central jet. Digital image analysis and analysis of wall pressure fluctuations were used for this characterization. Fluidization of two types of particles, glass and polypropylene (PP) was studied at two different initial bed heights of H/D = 1 and 2 with three central jet velocities 5, 10 and 20 m/s. Time averaged as well as dynamical characteristics were studied. The Eulerian-Eulerian two fluid model based on kinetic theory of granular flows was used to simulate these experiments. The predicted results were compared with the experimental data and previously published correlations. Although, there is agreement with experimental data in some aspects, complete agreement was not found. The presented experimental data and comparison with CFD predictions will provide useful basis for further work on understanding bubbling fluidized beds. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: CFD; fluidized beds; hydrodynamics; image analysis; pressure fluctuations; single jet

Fault detection and analysis of Kapton film in fuel cells using image processing - Firdous, R.; Aherrao, S.; Narute, B.; Borkar, V. (International Conference on Computing, Analytics and Security Trends, CAST 2016, 2017)
Fuel cell is one of the best alternatives of fossil energy in the modern scenario. But still there are some shortcomings such as durability and reliability, which block the wide application of fuel cells. To overcome these barriers, fault diagnosis is an efficient solution. This paper proposes a method for finding dimensional accuracies in Kapton films in membrane electrode assemblies (MEA) of fuel cells using image processing tools for offline fault analysis. © 2016 IEEE.
Keywords: Dimensional accuracy; Fault analysis; fault detection; Fossil energy; fuel cell; Gas fuel purification; image analysis; Image processing; Image processing tools; Kapton films; Membrane electrode assemblies; Offline; polyimides

Flow visualization by Matlab® based image analysis of high-speed polymer melt extrusion film casting process for determining necking defect and quantifying surface velocity profiles - Aarati Vagga; Swapnil Aherrao; Harshawardhan Pol; Vivek Borkar (Advanced Industrial and Engineering Polymer Research, 2022)
The primary objective of this research paper is to detect and quantify the necking defect and surface velocity profiles in high-speed polymer melt extrusion film casting (EFC) process using Matlab® based image processing techniques. Extrusion film casting is an industrially important manufacturing process and is used on an industrial scale to produce thousands of kilograms of polymer films/sheets and coated products. In this research, the necking defect in an EFC process has been studied experimentally and the effects of macromolecular architecture such as long chain branching (LCB) on the extent of necking have been determined using image processing methodology. The methodology is based on the analysis of a sequence of image frames taken with the help of a commercial CCD camera over a specific target area of the EFC process. The image sequence is then analyzed using Matlab® based image processing toolbox wherein a customized algorithm is written and executed to determine the edges of the extruded molten polymeric film to quantify the necking defect. Alongwith the necking defect, particle tracking velocimetry (PTV) technique is also used in conjunction with the Matlab® software to determine the centerline and transverse velocity profiles in the extruded molten film. It is concluded from this study that image processing techniques provide valuable insights into quantifying both the necking defect and the associated velocity profiles in the molten extruded film.
Keywords: Edge detection; Extrusion; Film; image analysis; Necking; Velocity measurement